2003
DOI: 10.2307/1543563
|View full text |Cite
|
Sign up to set email alerts
|

Genome Evolution in an Insect Cell: Distinct Features of an Ant-Bacterial Partnership

Abstract: Bacteria that live exclusively within eukaryotic host cells include not only well-known pathogens, but also obligate mutualists, many of which occur in diverse insect groups such as aphids, psyllids, tsetse flies, and the ant genus Camponotus (Buchner, 1965; Douglas, 1998; Moran and Telang, 1998; Baumann et al., 2000; Moran and Baumann, 2000). In contrast to intracellular pathogens, these primary (P) endosymbionts of insects are required for the survival and reproduction of the host, exist within specialized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 71 publications
3
17
0
Order By: Relevance
“…Using an approach to estimate the correlations after removing the effects of shared ancestry (39), the correlation coefficient for rRNA and tRNA gene copy numbers is 0.82, while the correlations between S and rRNA and tRNA gene copy numbers are 0.49 and 0.44, respectively (all values are highly statistically significant). While the phylogenetic relationships shown in Figure 1 are broadly consistent with those derived from analyses of other sequence data sets (45,46), there are some differences, such as Escherichia and Haemophilus being more closely related to each other than to Vibrio and Wigglesworthia lying within the radiation of Buchnera strains (47). However, we found that using alternative trees with such minor differences in topology had very little impact on the magnitude of the correlation coefficients.…”
Section: Resultssupporting
confidence: 72%
“…Using an approach to estimate the correlations after removing the effects of shared ancestry (39), the correlation coefficient for rRNA and tRNA gene copy numbers is 0.82, while the correlations between S and rRNA and tRNA gene copy numbers are 0.49 and 0.44, respectively (all values are highly statistically significant). While the phylogenetic relationships shown in Figure 1 are broadly consistent with those derived from analyses of other sequence data sets (45,46), there are some differences, such as Escherichia and Haemophilus being more closely related to each other than to Vibrio and Wigglesworthia lying within the radiation of Buchnera strains (47). However, we found that using alternative trees with such minor differences in topology had very little impact on the magnitude of the correlation coefficients.…”
Section: Resultssupporting
confidence: 72%
“…Genome sequencing indicates the loss of several genes and strong genome reduction compared to free-living relatives. This trait, shared with many symbionts in insect, is characteristic of maternally inherited bacterial symbionts lacking a free-living stage, and is thus congruent with previous findings (Gil et al, 2004;Wernegreen et al, 2003). In Cand.…”
Section: S Duperron Et Al: An Overview Of Chemosynthetic Symbioses supporting
confidence: 91%
“…comm. ;Wernegreen et al, 2003), and that the bacterium might also be involved in the production of pheromones used for food recruitment (Sauer, 2000). If Blochmannia provides a more subtle or sporadic selective advantage than is typical of nutritional P endosymbionts, it may exhibit a more labile host association.…”
mentioning
confidence: 99%